Review: Getting Under Our Skin: The Cultural and Social History of Vermin, by Lisa T. Sarasohn - Biehler, Dawn; Sarasohn, Lisa T. (University of California Press, 2025)
The inaugural issue of Animal History included a “Tracks in the Field” piece by Christopher Blakley that outlined the historiography of relationships among racism, enslavement, and human-animal studies. A comparable literature is accumulating that relates racism to creatures labeled as pests—some of it about the ecological and political conditions that expose racialized people to pests and pesticides, some of it about the very idea of pests as connected with abjection and disgust, and some interweaving the material and the discursive. Indeed, Blakley mentions some contributions to the slavery literature that address enslaved people’s role in pest control. Lisa Sarasohn’s book Getting Under Our Skin mostly focuses on human cultural representations of infestation with some of humankind’s most intimate other-than-human associates. The book shines important light on how “vermin” became associated with human hierarchy, dehumanization, and violent oppression.